PENYAKIT MIELOPROLIFERATIF - Putra Sedana, Made; Wulansari, T. Ivone (journal of internal medicine; Vol. 8, No. 1 Januari 2007, 2012)
Myeloproliferative disorder (MPD) represent a group of disease marked by cellular proliferation of one or more haematologic stem cells which include polycythemia vera, essential thrombocythemia, chronic idiopathic myelofibrosis with myeloid metaplasia / MMM, hypereosinophillic syndrome / HES, unclassified myeloproliferative disease / U-Mpd, chronic myelogenous leukemia / CML and chronic neutrophylic leukemia / CNL. The incidence and pathogenesis are still unknown. Chronicity which alterable to aggressive phase become acute leukemia and clonal cytogenetic abnormalities in erythroblast, neutrophyl, basophyl, macrophage, megakaryocytes and B-lymphocytes, but not in fibroblast are characteristics of the disease. Haematopoeisis is marked by autonomically growth and myeloid hyperplasia in bone marrow. Bone marrow aspiration show trilineage hypercellularity. The complications include thrombotic phenomenon, micro and macrovascular arteries thrombosis, bleeding phenomenon, hypercatabolism and transformation into acute myelogenous leukemia / AML. Pseudocoagulopathy, pseudohyperkalemia, pseudohyperacydphosphatemia, pseudohypoglicemia and pseudohypoxemia can be seen.
Keywords: MPD, complications